A SUSTAINABLE QUEUING SUPPLY CHAIN MODEL FOR GREENING ITEMS UNDER FUZZY ENVIRONMENT - Jai Deep Pandey; Mahesh Kumar; Geetanjali Sharma; Naeem Ahmad; Santosh Kumar; Khursheed Alam (Proceedings on Engineering Sciences)
Supply chain operations go well when demand is stable, but when demand fluctuates, the chain's behavior becomes unbalanced and its participants may face risks to their financial well-being. Demand rate fluctuations are referred to as having an imprecise nature. Because burning petrol and diesel releases numerous pollutants that harm the environment, it is to blame for carbon emissions. Nowadays, a popular term related to production inventory optimization for the greening effect and other policies is carbon emissions tax. Present paper deals with the application of queuing in supply chain management where demand is imprecise in nature and has been taken as a triangular fuzzy number under carbon emissions. In the final, we have minimized the total fuzzy inventory cost with the applications of queuing theory for the supply chain management under carbon emissions. Numerical examples have been verified for the model, and sensitivity analysis of inventory parameters has been taken for good utilizations in various industrial scenarios.